Principals’ Records-Keeping Practices and School Effectiveness in Ilorin Metropolis Secondary Schools - Olaifa, Adeseko Sunday; Fagbola, Simbiat Mojibola; Ayoku, Oba Baba; Sagaya, Abiodun Amudalatu; Hassan, Solawat Ajibola; Abolarin, Taibat Joke (Pedagogik: Jurnal Pendidikan, 2024)
The research focuses on the record-keeping practices of principals in public secondary schools in Ilorin metropolis, Kwara State, Nigeria. Two research questions and one research hypothesis were raised to guide the study. A descriptive survey research design was employed, allowing for self-reporting of information without manipulating variables. The sample included 121 principals and 155 vice principals from four Local Government Areas. The research instrument was a structured questionnaire, "Principals' Records Keeping Practices and School Effectiveness Questionnaire (PRMPSEQ)," developed from a literature review. The data was analysed using both descriptive and inferential statistics. The study found a positive correlation between these two aspects, indicating that effective records management is crucial for achieving high levels of school effectiveness. The study found a moderate level of effectiveness in principals' records-keeping practices, with areas for improvement identified in record retrieval, disposal, use and archiving. The Pearson Product Moment Correlation analysis reveals a significant positive correlation between principals' record-keeping practices and school effectiveness in public secondary schools in Ilorin metropolis, Kwara State, Nigeria. Overall, the findings provide valuable information for policymakers and school administrators in Ilorin metropolis, suggesting that enhancing records management practices could be a strategic approach towards improving school effectiveness and ultimately, the quality of education for students. The findings suggest that schools should prioritise continuous improvement in their records management systems, focusing on enhancing retrieval, disposal, utilisation, and archiving practices. Recommendations include enhancing records management training, implementing standardised systems, investing in technology and conducting regular audits.